Estimation of two species of urban plants for airborne particulates deposition: the influences of meteorological parameters and pollutants sources - Nur Dina Shazani Mohd Azam,; Shaharuddin Mohamad Ismail,; Ahmad Ainuddin Nuruddin,; Luqman Chuah Abdullah, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
In spite of being a part of the urban green infrastructures, urban forest is able to ameliorate the urban atmosphere through the deposition of particulates deposition on the surfaces of vegetations. The deposition is aided by the several factors such as boundary layer that exists on the surfaces of plants; the morphological characteristics as well as the meteorological parameters such as wind speeds, rainfall and mean temperature. This paper discusses on the role of urban plants (Ficus microcarpa and Acalypha siamensis) in capturing the airborne pollutants from various sources on the leaves surfaces. The findings showed that the elements’ concentration was greatly influenced by the meteorological parameters. Ca increases with the increased of wind speed (r = 0.702) at Jalan Hang Tuah, whereas at Country Heights Kajang, Mg was correlated to mean temperature (r = 0.795) and rainfall (r = 0.732); K, Cu, Th and PM were correlated to wind speed (r = 0.703, 0.777, 0.735 and 0.689 respectively); Rb and W were correlated to minimum temperature (r = 0.669 and r = 0.783 respectively) while Mn, W and PM were highly correlated to relative humidity (r = 0.839; r = 0.755) and r = 0.680 respectively). The meteorological parameters influence the deposition of pollutants is also due to the sites background and pollutants sources. The results also showed the elements with their possible sources; Country Heights Kajang: K and Ca (7.898%) were originated from construction while Sc, Ni, Cr, Ti and S (17.592%) were mainly emitted from sediments or road dust along Jalan Hang Tuah. Therefore, sustainability for good quality of urban air is achieved through the planting of more vegetation in urban areas.